1997
DOI: 10.1007/bf02783310
|View full text |Cite
|
Sign up to set email alerts
|

A fluorescence double-quenching study of native lipoproteins in an animal model of manganese deficiency

Abstract: Iodide and acrylamide were applied simultaneously in a double-quenching experiment to compare acrylamide quenching constants for internal and external fluorophores of high-density lipoproteins (HDL1 and HDL2) from manganese-adequate (MnA) and deficient (MnD) rats, free of the electrostatic effects associated with iodide. In MnA HDL1 compared to MnD HDL1, the acrylamide quenching constant for external fluorophores was different (P < 0.1). In MnA HDL2, there were two populations of fluorophores accessible to acr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2005
2005
2013
2013

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 26 publications
1
7
0
Order By: Relevance
“…The retardation of growth observed in MnD animals was independent of food intake. Retardation of rodent growth in Mn deficiency has also been reported by previous studies (Paynter 1980;Fahim et al 1990;Klimis-Tavantzis et al 1993;Taylor et al 1997) and it seems to be an effect of reduced efficiency of food conversion with dietary Mn depletion (Yang & Klimis-Tavantzis 1998a).…”
Section: Discussionmentioning
confidence: 54%
See 3 more Smart Citations
“…The retardation of growth observed in MnD animals was independent of food intake. Retardation of rodent growth in Mn deficiency has also been reported by previous studies (Paynter 1980;Fahim et al 1990;Klimis-Tavantzis et al 1993;Taylor et al 1997) and it seems to be an effect of reduced efficiency of food conversion with dietary Mn depletion (Yang & Klimis-Tavantzis 1998a).…”
Section: Discussionmentioning
confidence: 54%
“…The above Mn levels were chosen because studies indicate that a Mn level of less than 1.0 ppm results in Mn deficiency in about fourteen weeks (Klimis-Tavantzis et al 1993;Taylor et al 1997, Yang & Klimis-Tavantzis 1998a. About 10 ppm dietary Mn levels have been reported by the American Institute of Nutrition as an adequate level to prevent deficiency in the rat (Reeves et al 1993).…”
Section: Animal Carementioning
confidence: 99%
See 2 more Smart Citations
“…Previous studies have shown that Mn may affect blood pressure by decreasing the tension of isolated vascular tissue preparations in vitro [21]. However, there have been no animal studies to 0955 Our laboratory was the first to report that Mn plays an important role in maintaining integrity of blood vessels [22][23][24][25][26]. Manganese is involved in arterial glycosaminoglycan metabolism by affecting the total proteoglycan content of the aorta, altering the molecular weight and sulfation pattern of chondroitin sulfate in the same tissue and thus predisposing the vessel to lipid deposition, lipoprotein oxidation and CVD [24,25].…”
Section: Introductionmentioning
confidence: 97%